Authenticating Representation: Women's Quotas and Islamist Parties. Issue 4 (21st April 2016) - Ben Shitrit, Lihi
Abstract : The spread of women's quotas in legislative bodies across the world since the mid-1990s has become one of the most significant factors impacting levels of women's political representation (Dahlerup 2013; Krook 2009; Tripp and Kang 2008). In the Middle East, a region that has long held a place at the very bottom of global rankings of women's representation, the adoption of such quotas is transforming levels of representation (Kang 2009). But there is still much debate over the utility of quotas for women's meaningful participation in political life. There is now a well-established literature that examines the effects of quotas on women's descriptive or numerical representation. We have a fairly robust idea about the types of quotas that are appropriate for particular sets of electoral system contexts when the goal is to generate a target percentage of women elected to legislative bodies (Jones 2005; Larserud and Taphorn 2007). However, questions about whether and how quotas benefit women beyond the simple addition of several women parliamentarians to the political game remain contested. The various arguments for the utility of quotas rest mainly on two underlying propositions. The first is that quotas, by bringing more women to the political sphere, promote the substantive representation of women's interests. The second is that quotas have a symbolic effect. They help demonstrate that women are fit and able to govern and so contribute to countering women's historical exclusion from politics.